Transition to Novel Internet of Things Technology for Management of Groundwater Resources? Case of Cape Town, South Africa - Arinaitwe, Miriam (Department of Civil Engineering, 2024)
Groundwater is significant for humans and nature due to its varying extent, prevalence and natural quality. Effective management and protection of groundwater resources is essential and requires detailed knowledge and quantitative/qualitative characterisation of the aquifer. It is vital to confirm the groundwater parameters during hydrogeological investigations as groundwater depends on factors like geology, climate, lithology, slope and many others. However, there needs to be sufficient data to conduct these investigations and develop models for decision support in managing groundwater resources. In this study, Internet of Things (IoT) technology was applied to collect groundwater level data from a borehole to solve the problem of insufficient hydrogeological data. IoT provided consistent data collection, appropriate capacity to deal with immense records and ensured speedy and accurate information analysis. The interval resolution of collecting the IoT-based data was changed from 15 minutes to 24 hours to increase the battery life of the water level sensor to have continuous communication between the gateway and sensor. A combination of MODFLOW Software, Geographical Information System (GIS) and Analytic Hierarchy Process (AHP) techniques was then adopted to assess the groundwater processes related to Managed Aquifer Recharge (MAR) in the study area. This research investigates the workability of using IoT technology to collect groundwater level data to assess the processes that occur in the Cape Flats Aquifer around a stormwater pond catchment area. The study area in the Mitchells Plain West Catchment comprises the catchment areas of two stormwater ponds and covers an area of 0.315 km2 . The AHP and GIS techniques were used to produce a groundwater recharge potential zone map of the study area to develop a numerical groundwater model in MODFLOW. Recharge rates, hydraulic conductivities and other groundwater paraments were assigned and varied with estimated boundary conditions during model development. It was carried out based on acceptable ranges for the study area from previous studies and water resources management agencies of South Africa. The model was run and calibrated using the IoT-based groundwater levels collected at the monitoring borehole at Green dolphins pond. The study determined that the stormwater ponds were located in areas with very high groundwater recharge potential that covered 10.6% of the total study area. They are located in a flat area with quaternary deposits, low drainage density and high lineament density, which increase water infiltration rate, thus promoting groundwater recharge. The impact of the groundwater recharge was evaluated using the water budget, as there was an increase of 0.86 m between the observed head value and simulated head value at the monitoring borehole. It was observed that varying the recharge rates and hydraulic conductivity influences the fluctuations in the water table and the outflows presented in the water budget tables. Therefore, the increase in the water table at the borehole shows the importance of stormwater ponds as a water source for MAR.